2021
DOI: 10.3389/fphar.2021.731769
|View full text |Cite
|
Sign up to set email alerts
|

Guanxinkang Decoction Attenuates the Inflammation in Atherosclerosis by Regulating Efferocytosis and MAPKs Signaling Pathway in LDLR−/− Mice and RAW264.7 Cells

Abstract: Guanxinkang decoction (GXK), a traditional Chinese medicinal drug, is used to treat cardiovascular disease. The aim of the study was to investigate the effects of GXK on inflammation in LDLR−/− mice and RAW264.7 cells. Fed with high fat diet for 12 weeks, the mice were randomly divided into six groups, then administered with oral 0.9% saline or GXK (7.24, 14.48, and 28.96 g/kg) or Atorvastatin (1.3 mg/kg) for 12 weeks. RAW 264.7 cells were induced with ox-LDL or ox-LDL plus different concentrations of GXK (1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…2 ). Nevertheless, a similar phenomenon has also been observed in other studies [ 32 , 33 ], and this would not affect the conclusion that the protein levels of TNF-α and IL-6 in cell supernatants were reduced after simultaneous stimulation of EgCF and LPS compared with using LPS stimulation alone.…”
Section: Discussionsupporting
confidence: 85%
“…2 ). Nevertheless, a similar phenomenon has also been observed in other studies [ 32 , 33 ], and this would not affect the conclusion that the protein levels of TNF-α and IL-6 in cell supernatants were reduced after simultaneous stimulation of EgCF and LPS compared with using LPS stimulation alone.…”
Section: Discussionsupporting
confidence: 85%
“…The findings of Zhang et al demonstrated that treatment with Guanxinkang decoction attenuate atherosclerosis in mice by inhibiting inflammatory cytokine production mediated by downregulation of the MAPK signaling pathway. [ 26 ] Moreover, growing pieces of evidence from research have revealed a strong correlation between hyperglycemia and p38 MAPK signaling activation. [ 27 ] A study of Fan et al showed that treatment of streptozotocin and high fat diet (STZ‐HFD)‐induced diabetic rats with nesfatin‐1 attenuate cardiomyopathy by downregulating the p38 MAPK signaling pathway and associated cardiac apoptosis, fibrosis, inflammation, and oxidative stress.…”
Section: Involvement Of Various Cellular Pathways In Dcmmentioning
confidence: 99%